Fenologi Pohon Angsana (Pterocarpus indicus) Di Kota Manado. - Tepenur Weya; Johny S. Tasirin; Martina A. Langi; Josephus I. Kalangi (COCOS, 2016)
ABSTRACTThis research is aimed to study the phenology of angsana trees in the urban areas of Manado city. Sam Ratulangi street is divided into five observing segments with relatively the same number of trees at about 129-131 at each segment giving a total of 651 trees. The phenology observed at each tree including leaf, flower, and fruit phenomenon. The diameter of each tree are measured. Trees were then greuped into five categories:<10, 10-<20, 20-<30, 30-<40 and â‰¥40 cm. The results shows that angsana trees in Sam Ratulangi street had diameter of about 3.4-50.5 cm.The highest accumulation at trees was at last fourth categories ranging at 132-185 trunks. The phenology of leaves which dominate the entire segments on Sam Ratulangi street are green leaves at 89.9%of the 651 trees.The shoot phenology was performed by 11-20 trees (1.7-3.1%) and the flowering phenomena were found in 17-20 trees (2.6-3.8%). The flowering phenomena was mostly found at segment 1 (zero point) and becoming less and less toward the upper segments (Citraland intersection). The fruiting phenology shows and an opposite trend. The new flowering phenology are found on trees in three categories at medium diameters (10-40 cm) while the phenology of fruiting are found on trees with large diameters (>20 cm).